An Integrated Fibrosis Signature for Predicting Survival and Immunotherapy Efficacy of Patients With Hepatocellular Carcinoma - Liu, Long; Liu, Zaoqu; Meng, Lingfang; Li, Lifeng; Gao, Jie; Yu, Shizhe; Hu, Bowen; Yang, Han; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Molecular Biosciences, 2021)
Introduction: Fibrosis, a primary cause of hepatocellular carcinoma (HCC), is intimately associated with inflammation, tumor microenvironment (TME), and multiple carcinogenic pathways. Currently, due to widespread inter- and intra-tumoral heterogeneity of HCC, the efficacy of immunotherapy is limited. Seeking a stable and novel tool to predict prognosis and immunotherapy response is imperative. Methods: Using stepwise Cox regression, least absolute shrinkage and selection operator (LASSO), and random survival forest algorithms, the fibrosis associated signature (FAIS) was developed and further validated. Subsequently, comprehensive exploration was conducted to identify distinct genomic alternations, clinical features, biological functions, and immune landscape of HCC patients. Results: The FAIS was an independent prognostic predictor of overall survival (OS) and recurrence free survival (RFS) in HCC. In parallel, the FAIS exhibited stable and accurate performance at predicting prognosis based on the evaluation of Kaplan-Meier survival curve, receiver operator characteristic (ROC) curve, decision curve analysis (DCA), and Harrell's C-index. Further investigation elucidated that high-risk group presented inferior prognosis with advanced clinical traits and high mutation frequency of TP53, while the low-risk group was charactered by superior CD8+ T cells infiltration, higher TIS score, and lower TIDE score. Additionally, patients in low-risk group might yield more benefits from immunotherapy. Conclusion: The FAIS is an excellent scoring system could stratify HCC patients, which might serve as a promising tool to guide surveillance, improve prognosis, and facilitate clinical management.